To What Extent Do Exchange Rates and their Volatility Affect Trade? - Huchet-Bourdon, Marilyne (OECD Trade Policy Papers, 2011)
Trade deficits and surpluses are sometimes attributed to intentionally low or high exchange rate levels. The impact of exchange rate levels on trade has been much debated but the large body of existing empirical literature does not suggest an unequivocally clear picture of the trade impacts of changes in exchange rates. The impact of exchange rate volatility on trade also does not benefit from a clear theoretical cause-effect relationship. This study examines the impact of exchange rates and their volatility on trade flows in China, the Euro area and the United States in two broadly defined sectors, agriculture on the one hand and manufacturing and mining on the other. It finds that exchange volatility impacts trade flows only slightly. Exchange rate levels, on the other hand, affect trade in both agriculture and manufacturing and mining sectors but do not explain in their entirety the trade imbalances in the three countries examined